Effects of prenatal subjective well-being on birth outcomes and child development: A longitudinal study - Wanda Estinfort; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Yi-Yung Chen; Hsing Jasmine Chao; Ling-Chu Chien; Yu-Chun Lo; Yi-Hua Chen (European Psychiatry, 2022)
Abstract